A 3-D crustal shear wave velocity model and Moho map below the Semail Ophiolite, eastern Arabia. Issue 2 (16th June 2022) - Weidle, C; Wiesenberg, L; El-Sharkawy, A; Krüger, F; Scharf, A; Agard, P; Meier, T
SUMMARY: The Semail Ophiolite in eastern Arabia is the largest and best-exposed slice of oceanic lithosphere on land. Detailed knowledge of the tectonic evolution of the shallow crust, in particular during and after ophiolite obduction in Late Cretaceous times is contrasted by few constraints on physical and compositional properties of the middle and lower continental crust below the obducted units. The role of inherited, pre-obduction crustal architecture remains therefore unaccounted for in our understanding of crustal evolution and the present-day geology. Based on seismological data acquired during a 27-month campaign in northern Oman, Ambient Seismic Noise Tomography and Receiver Function analysis provide for the first time a 3-D radially anisotropic shear wave velocity ( VS ) model and a consistent Moho map below the iconic Semail Ophiolite. The model highlights deep crustal boundaries that segment the eastern Arabian basement in two distinct units. The previously undescribed Western Jabal Akhdar Zone separates Arabian crust with typical continental properties and a thickness of ∼40–45 km in the northwest from a compositionally different terrane in the southeast that is interpreted as a terrane accreted during the Pan-African orogeny in Neoproterozoic times. East of the Ibra Zone, another deep crustal boundary, crustal thickness decreases to 30–35 km and very high lower crustal VS suggest large-scale mafic intrusions into, and possible underplating of the Arabian continental crust that occurred most likely during Permian breakup of Pangea. Mafic reworking is sharply bounded by the (upper crustal) Semail Gap Fault Zone, northwest of which no such high velocities are found in the crust. Topography of the Oman Mountains is supported by a mild crustal root and Moho depth below the highest topography, the Jabal Akhdar Dome, is ∼42 km. Radial anisotropy is robustly resolved in the upper crust and aids in discriminating dipping allochthonous units from autochthonous sedimentary rocks that are indistinguishable by isotropic VS alone. Lateral thickness variations of the ophiolite highlight the Haylayn Ophiolite Massif on the northern flank of Jabal Akhdar Dome and the Hawasina Window as the deepest reaching unit. Ophiolite thickness is ∼10 km in the southern and northern massifs, and ≤5 km elsewhere.